Description of new species of Pseudogaurax Malloch (Diptera: Chloropidae) from Brazil, with notes on natural history - Carvalho-Filho, Fernando S.; Cruz, Vanessa C.; Monteiro, Nilton J. S.; Kloss, Thiago G. (Zootaxa, 2024)
Pseudogaurax Malloch is a genus of Chloropidae with about 70 described species found in all biogeographic regions, but several additional undescribed species are known. In this study we describe six new species from Brazil: Pseudogaurax alvinae sp. nov., Pseudogaurax amazonica sp. nov., Pseudogaurax braoculatus sp. nov., Pseudogaurax cyclosa sp. nov., Pseudogaurax primavera sp. nov., and Pseudogaurax wheeleri sp. nov. Pseudogaurax trifidus (Duda) and Pseudogaurax unilineatus Hall are newly recorded from South America, and Pseudogaurax tridens Sabrosky is newly recorded from the Brazilian Amazon. Data on host records are provided for P. alvinae sp. nov., P. braoculatus sp. nov., P. cyclosa sp. nov., P. tridens, P. trifidus, and P. trilineatus. The puparia of P. alvinae sp. nov., P. cyclosa sp. nov., and P. longilineatus Sabrosky are described as well.